Integration of Obese Children in Physical Education Sessions: An Exploratory Study - Bilel Aydi; Okba Selmi; Santo Marsigliante; Mohamed A. Souissi; Nizar Souissi; Antonella Muscella (MDPI AG, 2023)
We investigated the effect of the role of the joker in children with obesity (OCs) on integration and physio-psychological responses during small-sided games (SSG) training programs. Sixteen OC students (age 13.8 ± 0.73 years) performed training programs consisting of two sessions a week for three weeks. The experimental protocol consisted of 16 teams of 4 children (3 of normal weight and 1 OC). The 16 teams were divided into 2 groups, one with an OC playing as the joker (SSG-J) and the other group with OC playing as non-joker (SSG-NJ). Maximum heart rates (HRmax), blood lactate concentration [La] and OMNI-Child perceived exertion were measured at the end of each SSG. A physical activity enjoyment Scale (PACES) was accomplished during physical activity for the evaluation of feelings in OCs. Additionally, the profile of mood states (POMS) was measured before and after the SSG-J and SSG-NJ programs. HRmax, [La], perceived exertion, and PACES scores were significantly higher after the SSG-J compared with SSG-NJ (increments of 6.4%, 31.7%, 19.5% and 18.1%, respectively). The score of the POMS variables was positively increased in the presence of jokers. The vigor score increased by 30%, while tension and total mood disturbance scores decreased by 27.6% and 4.5%, respectively. These findings suggest that the joker role could be effective in improving integration, physical enjoyment, physiological responses and mood states in OCs when a team game is used during PE sessions. PE teachers could then program joker exercises with the aim of improving OCs' physical commitment willingness to play.